The Influence of Knowledge, Perception, Promotion, and Religiosity of the Community on the Interest in Becoming Customers of Islamic Banks - Ubaidillah Ubaidillah; Safian Yasmin Hanani Mohd; Farkhatul Lutviyati (Presscience, 2023)
Sharia banks are financial institutions that are operationally different from conventional banks. As a newcomer, the concept of sharia banking is experiencing a difficult situation because people are familiar with conventional banks so not many people understand about sharia banks. This research aims to determine the influence of knowledge, perception, promotion and community religiosity on interest in becoming sharia bank customers in the people of Purwokerto City, Banyumas Regency. This research uses a quantitative method by determining the sample using a simple radom sampling technique with a total of 400 respondents. The data source for this research is primary data. The data collection method was carried out using a questionnaire. Meanwhile, the data was analyzed using multiple linear regression analysis. This research variable consists of independent variables which include knowledge, perception, promotion and religiosity, as well as a dependent variable regarding people's interest in becoming sharia bank customers. Partially, the variables knowledge, perception, promotion and religiosity have a significant positive effect on people's interest in becoming sharia bank customers. Then simultaneously the variables of knowledge, perception, promotion and religiosity influence the interest of the people of Purwokerto City to become sharia bank customers.